Suppression of Plant Immune Responses by the Pseudomonas savastanoi pv. savastanoi NCPPB 3335 Type III Effector Tyrosine Phosphatases HopAO1 and HopAO2 - Castañeda-Ojeda, María Pilar; Moreno-Pérez, Alba; Ramos, Cayo; López-Solanilla, Emilia (Frontiers in Plant Science, 2017)
The effector repertoire of the olive pathogen P. savastanoi pv. savastanoi NCPPB 3335 includes two members of the HopAO effector family, one of the most diverse T3E families of the P. syringae complex. The study described here explores the phylogeny of these dissimilar members, HopAO1 and HopAO2, among the complex and reveals their activities as immune defence suppressors. Although HopAO1 is predominantly encoded by phylogroup 3 strains isolated from woody organs of woody hosts, both HopAO1 and HopAO2 are phylogenetically clustered according to the woody/herbaceous nature of their host of isolation, suggesting host specialization of the HopAO family across the P. syringae complex. HopAO1 and HopAO2 translocate into plant cells and show hrpL-dependent expression, which allows their classification as actively deployed type III effectors. Our data also show that HopAO1 and HopAO2 possess phosphatase activity, a hallmark of the members of this family. Both of them exert an inhibitory effect on early plant defence responses, such as ROS production and callose deposition, and are able to suppress ETI responses induced by the effectorless polymutant of P. syringae pv. tomato DC3000 (DC3000D28E) in Nicotiana. Moreover, we demonstrate that a ΔhopAO1 mutant of P. savastanoi NCPBB 3335 exhibits a reduced fitness and virulence in olive plants, which supports the relevance of this effector during the interaction of this strain with its host plants. This work contributes to the field with the first report regarding functional analysis of HopAO homologs encoded by P. syringae or P. savastanoi strains isolated from woody hosts.